User‐centered design features for digital health applications to support physical activity behaviors in solid organ transplant recipients: A qualitative study. Issue 12 (23rd September 2021) - Mathur, Sunita; Janaudis‐Ferreira, Tania; Hemphill, Julia; Cafazzo, Joseph A.; Hart, Donna; Holdsworth, Sandra; Lovas, Mike; Wickerson, Lisa
Abstract: Introduction: Digital health tools may be effective in engaging solid organ transplant (SOT) recipients in physical activity (PA). This study examined the perspectives of SOT recipients regarding PA, and desired features for digital health tools. Methods: Semi‐structured interviews were used to explore perspectives of SOT recipients about barriers and motivators to physical activity, and core features of a digital health tool to support PA. Interviews were analyzed via thematic analysis. Results: Participants included 21 SOT recipients (11 men, 10 women, 21‐78 years, 1.5‐16 years post‐transplant) from various organ groups (four heart, five kidney, five liver, three lung, and four multi‐organ). Barriers to PA included risk aversion, managing non‐linear health trajectories, physical limitations and lack of access to appropriate fitness training. Facilitators of PA included desire to live long and healthy lives, renewed physical capabilities, access to appropriate fitness guidelines and facilities. Desired features of a digital health tool included a reward system, affordability, integration of multiple functions, and the ability to selectively share information with healthcare professionals and peers. Conclusions: SOT recipients identified the desired features of a digital health tool, which may be incorporated into future designs of digital and mobile health applications to support PA in SOT recipients.